Original paperThe relationship between vitamin D deficiency and coronary artery ectasia - Demir, Mehmet; Demir, Canan; Keçeoğlu, Serdar (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2014)
Introduction : The pathophysiology of coronary artery ectasia (CAE) has not been clearly identified although multiple abnormalities including arteritis, endothelial dysfunction, and atherothrombosis have been reported. The role of vitamin D deficiency suggests cardiovascular diseases such as coronary artery disease, heart failure, and hypertension. Vitamin D deficiency activates the renin-angiotensin-aldosterone system, which affects the cardiovascular system. For this reason, it could be suggested that there is a relationship between vitamin D deficiency and CAE. Aim: We aimed to compare the 25-OH vitamin D levels of CAE patients with those of controls. Material and methods : This study included 50 CAE patients (20 male, mean age: 60.26 ±10.6 years) and 30 controls (10 males, mean age: 57.86 ±11.6 years). Along with routine tests, 25 OH vitamin D and parathormone (PTH) levels were analysed. Twenty-five OH vitamin D and PTH levels were compared. Results : No statistically significant difference was found between the two groups in terms of basic characteristics. The average PTH level of the group of patients with CAE was higher than the average PTH level of the controls (97.8 ±46.3 pg/ml vs. 59.1 ±23.7 pg/ml; p < 0.001). The average 25 OH vitamin D level of the group of the patients with CAE was lower than the average 25 OH vitamin D level of the control group (18.9 ±8.5 ng/ml vs. 31.3 ±11.2 ng/ml; p < 0.001). Conclusions : An association between CAE and vitamin D deficiency was found in our study.